Extensive experimental validation of a model for pneumatic drying of cassava starch - Chapuis, Arnaud; Lancement, Charlene; Giraldo, Francisco; Precoppe, Marcelo; Moreno, Martín; Dufour, Dominique; Tran, Thierry (Informa UK Limited, 2023)
A pneumatic drying model, developed in a previous work, was tested and validated based on a series of 56 experiments of cassava starch drying conducted on a pilot-scale pneumatic dryer. After fitting two parameters, the average diameter of starch particles and a heat loss factor, the model predicted the effects of main operating conditions with a level of accuracy comparable to that of the experimental measurements. Transient phases with sudden variations of product feed rate were also successfully simulated. The model is therefore suitable for equipment design purposes. The experimental results showed that the size of starch particles considerably decreases with increasing air velocity. As a result, at high air velocity, despite the shorter residence time in the drying pipe, the overall drying performance is improved due to the smaller particle size. It is therefore possible to increase air velocity, and hence product feed rate and production capacity, without detrimental effect on the drying efficiency.